Matrine reduces susceptibility to postinfarct atrial fibrillation in rats due to antifibrotic properties. (27th February 2018) - Ma, Jin; Ma, Shiyu; Yin, Chunxia; Wu, Huanlin
Abstract: This study aimed to investigate whether matrine could prevent atrial fibrillation (AF) after myocardial infarction by reducing left atrial fibrosis, and to determine the underlying mechanisms in isolated cardiac fibroblasts (CFs). Five weeks after MI, matrine‐treated rats had lower rates of AF inducibility and shorter AF duration than MI rats. Matrine improved the left atrial conduction velocity and homogeneity. Matrine decreased the fibrosis positive areas and the protein levels of type I collagen and type III collagen in the left atrium. Matrine inhibited CFs differentiation to myofibroblasts and the expression of transforming growth factor‐beta 1 and matrix metalloproteinase 9. In vitro, matrine inhibited the CFs proliferation, migration, differentiation, and secretion ability. These in vitro and in vivo data demonstrated that matrine has the potential to reduce susceptibility to AF after MI due, at least in part, to reduced atrial fibrosis via inhibiting CFs proliferation, migration, differentiation, and secretion ability.